A review of lentil (Lens culinaris Medik) value chain: postharvest handling, processing, and processed products - Yeboah, Charlotte Oduro; Sulaiman, Rabiha; Uebersax, Mark A.; Dolan, Kirk D. (Wiley Periodicals, 2022)
Lentils (Lens culinaris Medik.) are grown worldwide in diverse agroecological regions with significant global production and trade. Since early 2000s, lentils production and consumption have been growing beyond its traditional areas of production and utilization, notably in USA, Canada, Australia, UK, and many European Union countries. Lentils are a rich source of protein, minerals, and many bioactive compounds. Therefore, lentil-based products can offer a healthy food choice for all consumers, including those who are vegetarian or vegans, and/or looking for meat protein alternatives due to health and/or environmental concerns. In order to avail all the benefits that lentils offer, a quality maintenance approach is essential across value-chain operations of postharvest handling, storage, and value-added processing. In recent years, lentils have been used increasingly in a variety of value-added products and cuisines in the developed countries. Different processing methods, for example, cooking, autoclaving, extrusion, baking, roasting, fermentation, and sprouting, significantly improve protein bioavailability, total digestibility, and overall nutritional and organoleptic quality. A number of traditional and innovative processing techniques also have been used to produce lentil-based end-products or ingredients for various food applications. Overall, lentils are well positioned as a food legume crop to cater to emerging trends among consumers, especially those looking for healthy food choices, an alternative plant-based protein for global food security, and foods that are produced in environmentally friendly and agriculturally sustainable manner. Significant production and consumption trends for lentils clearly demonstrate enhanced value for consumers and further impact in contributions to a nutritious global food supply.